RESEARCH OF FORMATION LEVELS INTELLECTUAL SKILLS OF HIGH SCHOOL STUDENTS (Pedagogy of Higher and Secondary Education, 2007)
In article results of an experimental research of levels of formation intellectual skills logically to operate with a teaching material at learning senior classes of secondaiy school are submitted.